A community college instructor like me: Race and ethnicity interactions in the classroom - Robert W. Fairlie; Florian Hoffmann; Philip Oreopoulos (University of California, Economics Department, 2014)
Administrative data from a large and diverse community college are used to examine if underrepresented minority students benefit from taking courses with underrepresented minority instructors. To identify racial interactions we estimate models that include both student and classroom fixed effects and focus on students with limited choice in courses. We find that the performance gap in terms of class dropout rates and grade performance between white and underrepresented minority students falls by 20 to 50 percent when taught by an underrepresented minority instructor. We also find these interactions affect longer term outcomes such as subsequent course selection, retention, and degree completion.
Keywords: 330; minority; college; community college; affirmative action; diversity